Weisheit - Mazzinghi, Luca (W. Kohlhammer GmbH, 2018)
This commentary for the first time combines all relevant aspects for the interpretation of this late text in the Old Testament/Apocrypha: textual criticism, philological and literary analysis; the dual historical context with the link to Hellenistic environment, on the one hand, and to the biblical tradition on the other; and finally, the - highly innovative - theology of the Book of Wisdom. Aspects of reception history and hermeneutic issues complete the commentary. Erstmals führt der vorliegende Kommentar alle Aspekte zusammen, die für die Interpretation dieser Spätschrift des Alten Testaments relevant sind: Textkritik, philologische und literarische Analyse; der zweifache historische Kontext mit der Verbindung zur griechisch-hellenistischen Umwelt einerseits und zur biblischen Tradition andererseits; schließlich die - sehr innovative - Theologie des Buchs der Weisheit. Aspekte der Rezeptionsgeschichte und hermeneutische Fragen runden die Kommentierung ab
Keywords: Gender; Hellenismus; Sapientia Salomonis